WAKAF KONTEMPORER, DARI TEORI KE APLIKASI - A. Faishal Haq (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2014)
In the formulation of classical fiqh, Islamic charitable Endowments understood as tangible fixed assets, such as land and buildings, but in line with the rate of growth of a dynamic civilization, and offer new ideas on the concept of waqf endowments berfariasi which include cash which is a form of charitable funds or money collected by institutions managing waqf (na>zir) through the issuance of cash waqf certificate purchased by the public. The scholars' also gives the sense that the cash waqf property can be interpreted mewakafkan cash or securities maintained by the institution or financial institution Shariah perbankkan whose profits would wherewithal but the capital can not be reduced to donate, while the waqf funds collected can then be rolled out and invested by nadzir into various business sectors lawful and productive, so that profits can be utilized for the development of the people and the nation as a whole.